The Implementation of Digital Marketing In SME's: Opportunities and Challenges During The Covid-19 Pandemic: digital marketing, Coronavirus pandemic. - Sudarmiatin, Sudarmiatin; Fitriana; Hidayati, Nurul (Indonesian Journal of Business and Entrepreneurship, 2023)
During the Covid 19 Pandemic, the survival of Small and Medium Enterprises (SMEs) was threatened with bankruptcy due to the decline in people's incomes, and the implementation of Large-Scale Social Restrictions (PSBB). This study aims to (a) Identify the problems faced by SMEs in running their business during the Covid 19 Pandemic (b) Analyze the opportunities and challenges of SMEs in implementing digital marketing, and (c) develop digital marketing models to improve the performance of SMEs during the Covid 19 Pandemic. This research is a case study, which is a study that aims to help solve problems faced by the community including Small and Medium Enterprises. The subjects of this study were 12 SMEs in 3 cities and regencies in East Java which are engaged in retail, food and beverage and handicrafts. Research data collection was carried out using in-depth interviews, observation and documentation methods. Data analysis uses SWOT analysis to analyze digital marketing strategies during the Covid 19 pandemic. The results of the study show that the Covid 19 pandemic has greatly impacted the survival of SMEs. At the beginning of the Covid 19 pandemic, the sales turnover of retail and food and beverage SMEs decreased by 40%. But a few months later, SMEs began to rise and adjust to changes during the pandemic. By utilizing digital-based marketing strategies, retail and food and beverage SMEs are able to survive during the pandemic. However, for handicraft SMEs, there was a decline of up to 80%. In the new normal era such as today, marble handicraft SMEs have not recovered, some of them have even gone out of business because they are unable to bear operational costs. It is suggested that the local government should intervene to solve distribution problems to the export market. Keywords: digital marketing, Covid 19 pandemic, SMEs, SWOT